Representasi Konflik Ibu Tunggal dan Anak dalam Film Susah Sinyal - Han, Muhammad Ibtissam (KOMUNIKA: Jurnal Dakwah dan Komunikasi, 2018)
Susah Sinya Movie tells the conflict between single mother and her child. In this film the condition of a single mother who should raise a child without the presence of a husband experienced various conflicts with his son. This study attempts to illustrate how conflicts occur between a single mother and her child and their resolution, depicted in the Susah Sinyal film. This film illustrates the current phenomenon of single mothers who are too busy with work and less attention to their children that cause disharmonization.